The Effect of Groundwater Content on The Growth of Patchouli (Pogostemon cablin) in Batu Putih Village, Batu Putih District, Kolaka Utara Regency - Herwansah, Herwansah; Yanti, Yanti; Maretik, Maretik (Universitas Sembilanbelas November Kolaka, 2022)
Patchouli plants (Pogostemon cablin) in Batu Putih Village often die from erratic seasons. Excess soil water content during the rainy season causes plants to rot and die. In other cases, the death of patchouli is also caused by a lack of water content in the soil. This study aims to determine the effect of soil water content on the growth of patchouli (Pogostemon cablin) in Batu Putih Village, Batu Putih District, and North Kolaka Regency. This study used a randomized block design (RBD) method with two treatment factors, namely the material type and the groundwater concentration. Each type of material consisted of patchouli, soil and water, while the groundwater concentration consisted of watering 100% (500 ml), 60% (300 ml) and 40% (200 ml). The results showed that watering with 100% groundwater concentration (500 ml) gave the best growth compared to water at 60% and 40% groundwater concentrations. However, the results of the Anova test showed that watering with 100%, 60%, and 40% groundwater concentrations did not have a significant effect on plant growth, it was suspected that water was not the dominant factor in the patchouli plant growth process. Â Keywords: Patchouli, growth, soil moisture content, Pogostemon cablin.